DESAIN PROGRAM SIMULASI PENERAPAN KODE BOSE CHAUDHURI HOCQUENGHEM PADA DIRECT SEQUENCE SPREAD SPECTRUM - Ullum Azhari, M. Husnul; Pramaita, Nyoman; Diafari Djuni H, I Gst A. Komang (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p8, 2020)
This study proposes a design of simulation program for implementing Bose Chaudhuri Hocquenghem (BCH) code on Direct Sequence Spread Specterum (DSSS) to knowing the performance of the effect of DSSS with flat fading channel and AWGN without BCH code (7,4) with the application of BCH code (7,4) on DSSS with flat fading and AWGN channel. This simulation consist of simulation of BER application of BCH code (7,4) on DSSS with flat fading and AWGN channel, simulation of BER application code BCH (7,4) on DSSS with AWGN channel, simulation of the effect of Eb/No on noise variance in the DSSS system, and BER simulation as a function of noise variance on the DSSS system. Simulation of application BCH code (7,4) on DSSS with flat fading and AWGN channel analyzed based on Bit Error Rate (BER) versus Energy Bit per Noise (Eb/No). The application of BCH code (7,4) on DSSS with flat fading channel and AWGN shows better performance than DSSS with flat fading channels and AWGN without BCH coding (7,4). On the Eb/No value 10 dB, simulation application BCH code (7,4) on DSSS with flat fading channel and AWGN generate BER value which is approaching 0 with BER value 0.0188, while the DSSS simulation with flat fading channel and AWGN without BCH code (7.4) generate a BER value of 0.0228.